POLA KEPEMILIKAN DAN PENGELOLAAN HARTA BERSAMA PADA KELUARGA PEKERJA MIGRAN INDONESIA DI LAMPUNG TENGAH - Adinda Putri Ayuni; Taufid Hidayat Nazar; Muhamad Andriyanto; Nazar, Taufid Hidayat (Center of Gender Studies and Child of State Islamic Institute of Metro, 2024)
This study was conducted in Sri Pendowo Village, Central Lampung, to examine the patterns of ownership and management of joint assets in Indonesian migrant worker (PMI) families. Using a qualitative approach with in-depth interviews involving five families, the study revealed that three out of five families recorded assets under the wife's name, reflecting the significant role of wives as the primary breadwinners. The other two families adopted a joint ownership pattern without emphasizing a specific owner. Asset management was largely directed toward daily needs, home renovation, education, and investment, with some families managing income through collective savings such as arisan. These findings highlight that asset management patterns reflect family collaboration, despite differences in the recording of asset ownership. Keywords: Migrant Workers, Asset Ownership, Asset Management, Remittance, Family